Metoprolol prevents neuronal dendrite remodeling in a canine model of chronic obstructive sleep apnea - Yang, Lin; Zhao, Jing; Qu, Yang; Sun, Qiang; Li, Ting-ting; Yan, Mei-ling; Duan, Ming-jing; Li, Ke-xin; Wang, Yan-ru; Huang, Si-yu; Zhang, Shuai; Li, Yue; et al. (Acta pharmacologica Sinica, 2020)
Obstructive sleep apnea (OSA) is closely associated with central nervous system diseases and could lead to autonomic nerve dysfunction, which is often seen in neurodegenerative diseases. Previous studies have shown that metoprolol prevents several chronic OSA-induced cardiovascular diseases through inhibiting autonomic nerve hyperactivity. It remains unclear whether chronic OSA can lead to dendritic remodeling in the brain, and whether metoprolol affects the dendritic remodeling. In this study we investigated the effect of metoprolol on dendrite morphology in a canine model of chronic OSA, which was established in beagles through clamping and reopening the endotracheal tube for 4 h every other day for 12 weeks. OSA beagles were administered metoprolol (5 mg· kg −1 · d −1 ). The dendritic number, length, crossings and spine density of neurons in hippocampi and prefrontal cortices were assessed by Golgi staining. And the protein levels of hypoxia-inducible factor-1α (HIF-1α) and brain-derived neurotrophic factor (BDNF) were measured by Western blotting. We showed that chronic OSA successfully induced significant brain hypoxia evidenced by increased HIF-1α levels in CA1 region and dentate gyrus of hippocampi, as well as in prefrontal cortex. Furthermore, OSA led to markedly decreased dendrite number, length and intersections, spine loss as well as reduced BDNF levels. Administration of metoprolol effectively prevented the dendritic remodeling and spine loss induced by chronic OSA. In addition, administration of metoprolol reversed the decreased BDNF, which might be associated with the metoprolol-induced neuronal protection. In conclusion, metoprolol protects against neuronal dendritic remodeling in hippocampi and prefrontal cortices induced by chronic OSA in canine.